Ameliorative effects of curcumin towards cyclosporine-induced genotoxic potential: an in vitro and in silico study. (3rd July 2018) - Shah, Ankita J.; Prasanth Kumar, Sivakumar; Rao, Mandava V.; Pandya, Himanshu A.
Abstract: Several studies documented the ameliorative effects of curcumin which plays a pivotal role in radical scavenging activities. It also participates in various cellular pathways and interacts with multiple targets. In the present study, we investigated the ameliorative effect of curcumin upon chromosomal genotoxicity induced by cyclosporine, an immunosuppressant, using in vitro approaches. A plausible mechanism of how curcumin mitigates the genotoxic implications of cyclosporine was ascertained using in silico tools. We observed that the curcumin reduces the genotoxic consequences made by cyclosporine upon cell cycle checkpoints and associated chromosomal/DNA manifestations. In addition, we presented the mechanistic details of curcumin interaction with various biomacromolecule types using docking experiments which showed that the possible radical scavenging activities can only be emerged by inducing the expression of antioxidant enzymes, supported by available experimental evidences. We anticipate that the induction of antioxidant enzymes by curcumin would activate Nrf2-Keap1 pathway as the plausible mechanism to exert anti-inflammatory response as demonstrated in renal epithelial cells.